Are All Smiles Created Equal? How Emotional Contagion and Emotional Labor Affect Service Relationships - Hennig-Thurau, Thorsten; Groth, Markus; Paul, Michael; Gremler, Dwayne D. (Journal of Marketing, 2006)
In this study, the authors examine the effects of two facets of employee emotions on customers’ assessments of service encounters. Drawing on emotional contagion and emotional labor theories, they investigate the influence of the extent of service employees’ display of positive emotions and the authenticity of their emotional labor display on customers’ emotional states and, subsequently, on customers’ assessments of the service interaction and their relationship with the service provider. To test the study hypotheses, 223 consumers participated in a simulated service encounter in which actors played the roles of service employees. In a 2 × 2 factorial design, the employees varied both the extent of their smiling behavior and their emotional labor display by engaging in surface or deep acting. The results show that the authenticity of employees’ emotional labor display directly affects customers’ emotional states. However, contrary to expectations, the extent of employee smiling does not influence customer emotions, providing no support for the existence of primitive emotional contagion in service interactions. Furthermore, employee emotions exert an influence on customer outcomes that are of interest to marketers.